EFFECT OF SOLUS PER AQUA (SPA) ON INFANT WEIGHT - Agrystina Ryma Melati; C Tjahjono Kuntjoro; Sri Sumarni, Kamilah Hidayati; Rr. Sri Endang Pujiastuti (Belitung Raya Foundation, 2017)
Background: The prevalence of skinny infants in Indonesia is still high. Baby's Spa is considered to be able increase infant's weight. Objective: To determine the effectivity of baby spa in infant weight in in Bebengan Village, Boja Sub District, Kendal Regency, Central Java, Indonesia Methods: This study was a quasy-experimental study with non-equivalent control group design. There were 38 infants were selected using purposive sampling, divided into 3 groups, namely: 1) a group received Spa 2 times per week (12 infants), 2) a group received spa 3 times per week (13 infants), and 3) a control group. Baby digital scale of ARN-EBSD-04 was used to measure infant weight. Data were analyzed using paired t-test and ANOVA. Results: There was statistically significant effect of intervention in each group on the infant's weight. However, the data showed that the intervention that had a better effect on infant weight was the intervention of spa in two times per week with mean difference before and after intervention of 603 g. Conclusions: Spa in 2 times per week could significantly increase infant weight effectively. Therefore, it is recommended for midwife to apply this intervention to increase the weight gain of babies and to reduce the number of skinny infants in Indonesia.